GE_GERICHTE P/3536/2012 vom 18. Juni 2013 - GE Cour de justice (2013)
NULLA POENA SINE LEGE; IMPUTATION; DÉTENTION(INCARCÉRATION); INDEMNITÉ(EN GÉNÉRAL); HONORAIRES; TORT MORAL | CP.1; CP.51; CPP.11.1; CPP.429.1.a; CPP.429.1.c; CPP.431.2